Emergence and Evolution of the Journal of Bangladesh College of Physicians and Surgeons: Igniting the Professionalism - Ahmed, Tanveer; Yunus, Emran Bin; Rahman, Aminur; Md Nazmul Ahasan, Hasan Askari; Rahman, Masroor ur; Mostafi, Mamun; Chowdhury, MA Jalil; Mohammad, Quazi Deen; Haq, Syed Atiqul (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Journal of Bangladesh College of Physicians and Surgeons (JBCPS), all the go by ‘BCPS Journal’, is the official organ of BCPS inclusive of academic, extra-academic and official matters. The journal started its journey in August 1983, now in the fourth decades is embedded in the fanfare of Golden Jubilee of BCPS. It commensurate with the fellows’ desire that a supplement of the JBCPS shall be published as the official organ of the college on behalf of the education, training, research and publication to Showcase the college image in the academic arena. The special editorial board is tasked to marinate a document of the sojourn of the JBCPS, for now and then. The authors have tried to pick up pieces of information from all available local libraries and online resources to build up an edifice to be added on from time to time. It has been tried to fullfill the mandate through expanded and extended search and find the tenets of the emergence and evolution of the JBCPS with an endeavor to bring out a canvas of the paintings of the stories of the Odyssey. Bangladesh Medical Journal (BMJ) published by Bangladesh Medical Association (BMA) is the oldest journal of the country first published 50 years ago in July 1972. Then the Bangladesh Medical Research Council Bulletin (BMRC Bulletin), published in December 1975. JBCPS is the third in this sequence. Prof Golam Rasul was the first editor in chief and so far, fifteen chiefs navigated the journal so far. The first editorial board consisted of five members and present editorial board embracing almost all the subjects including editors from abroad. JBCPS is online since 2004 and is available in the Bangladesh Journals Online (BanglaJOL) since 2006. With Continued relentless untiring efforts of the editorial board and collaboration from the executive committee of BCPS the JBCPS is now one of the top ranked & prestigious peer reviewed journal of the country. The next endeavor shall be to enlist the journal in PubMed which is expected very soon. J Bangladesh Coll Phys Surg 2022; 40: 28-38